Construction of chromosome segment substitution lines of Dongxiang common wild rice (Oryza rufipogon Griff.) in the background of the japonica rice cultivar Nipponbare (Oryza sativa L.) - Ma, Xiaoding (Plant physiology and biochemistry : PPB, 2019)
Copyright © 2019 Elsevier Masson SAS. All rights reserved.